Liesegang Phenomenon of Liquid Metals on Au Film. Issue 7 (16th December 2022) - Xing, Zerong; Zhang, Genpei; Ye, Jiao; Zhou, Zhuquan; Gao, Jianye; Du, Bangdeng; Yue, Kai; Wang, Qian; Liu, Jing
Abstract: Room temperature liquid metals (LM) such as gallium (Ga) own the potential to react with specific materials which would incubate new application categories. Here, diverse self‐organized ring patterns due to nonequilibrium reaction‐diffusion and spreading‐limitation of Ga‐based LM clusters on gold (Au) film are reported, among which diffusion is the controlling step and the self‐limiting oxide layer plays the role of kinetic barrier. Such phenomena, classically known as the Liesegang rings, mainly occur in electrolyte media. Unlike existing systems, the present periodic crystallization mechanism enables highly symmetric spatiotemporal periodic Liesegang rings on a smaller scale under ambient conditions. Typically, the Ga‐Au and eutectic gallium‐indium alloy (EGaIn)‐Au reaction‐diffusion‐spreading systems are constructed, obtaining the revert type and hybrid type concentric Liesegang patterns, respectively. The competitive patterning behavior of the intermediate phase products AuGa2 and AuIn2 in hybrid Liesegang patterns is further analyzed by altering the initial Ga/In mass ratio, first‐principles calculations, and molecular dynamic simulations. When the mass ratio of In in GaIn alloy exceeds 15%, it will preferentially react with Au. The discovery of LM Liesegang phenomenon is expected to be a flashpoint for self‐organized reaction‐diffusion systems and offers promising rules for diverse areas such as materials synthesis and the jewelry design industry. Abstract : The phenomena and mechanisms for achieving Liesegang patterns of spatially recurrent crystallization through gallium (Ga)‐based liquid metal clusters dabbed onto the gold (Au) film have been disclosed. During the reaction‐diffusion‐spreading process of Ga‐based liquid metal clusters on Au film, the chemical reactions occur simultaneously, accompanied by the crystallization of intermediate phase products AuGa2 and AuIn2 .